The Multivariate Algorithmic Revolution and Beyond Essays Dedicated to Michael R. Fellows on the Occasion of His 60th Birthday - Bodlaender, Hans L.; Downey, Rodney; Fomin, Fedor V.; Marx, Dániel (Theoretical Computer Science and General Issues,, 2012)
Parameterized complexity is currently a thriving field in complexity theory and algorithm design. A significant part of the success of the field can be attributed to Michael R. Fellows. This Festschrift published in honor of Mike Fellows on the occasion of his 60th birthday. It contains 20 papers that showcase the important scientific contributions of this remarkable man describes the history of the field of parameterized complexity, and also reflects on other parts of Mike Fellows's unique and broad range of interests, including his work on the popularization of discrete mathematics for young children. The volume contains several surveys that introduce the reader to the field of parameterized complexity and discuss important notions, results, and developments in this field.